Overview and first year progress of the Widely scalable Mobile Underwater Sonar Technology H2020 project*. Issue 23 (2016) - Indiveri, Giovanni; Antonelli, Gianluca; Arrichiello, Filippo; Caffaz, Andrea; Caiti, Andrea; Casalino, Giuseppe; Volpi, Nicola Catenacci; de Jong, Ivan Bielic; De Palma, Daniela; Duarte, Henrique; Gomes, Joao Pedro; Grimsdale, Jonathan; et al.
Abstract: The Widely scalable Mobile Underwater Sonar Technology (WiMUST) project is an H2020 Research and Innovation Action funded by the European Commission. The action's main goal is to develop robotic technologies exploiting Autonomous Underwater Vehicles (AUVs) for geotechnical surveying and geophysical exploration. The paper briefly describes the project and its state of the art after the first year of activities.